Pengaruh E-Commerce dan Implementasi Sistem Informasi Akuntansi Terhadap Kinerja Bisnis Wirausaha Rintisan Mahasiswa - Herina Erpiani (2021)
This study aims to examine the effect of e-commerce and the implementation of accounting information systems on the business performance of student startups. The sample used in this study were students at the Pembangunan Nasional Veteran University, Jakarta. The sample selection technique in this study used purposive sampling and random sampling by setting certain criteria and collecting 35 respondents. Hypothesis testing in this study using Multiple Linear Regression with SPSS 26.0 for windows program. The results in this study include: e-commerce has a positive effect on the student entrepreneurship business performance and the implementation of accounting information systems has no effect on the student entrepreneurship business performance.